Feed muscle, shrink fat diet 6 weeks to the best shape of your life - Smith, Kathy 1951- (Meredith Books, 2008)
Muscle burns calories, even when you're at rest, but fat just sits there. After age 30, you start losing calorie-burning muscle and gain fat--and if you diet by eating the wrong foods and not exercising, you risk losing even more precious muscle. Fitness expert Smith shows you how to keep muscles strong and active by eating the right foods and doing the right combination of exercises.--From publisher description.